2010
DOI: 10.1590/s0103-84782010005000017
|View full text |Cite
|
Sign up to set email alerts
|

Adição de complexo enzimático e da granulometria da soja integral desativada melhora desempenho de frangos de corte

Abstract: IVAdição de complexo enzimático e da granulometria da soja integral desativada melhora desempenho de frangos de corte Addition of enzymatic complex and deactivated full-fat soybean particle size optimize performance of broilers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
1
5
0
1
Order By: Relevance
“…Similar results were obtained by ZOU et al (2006) andOPALINSKI et al (2010) while feeding broilers with diets with and without β-mannanase over the period of 1 and 21 days of age.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Similar results were obtained by ZOU et al (2006) andOPALINSKI et al (2010) while feeding broilers with diets with and without β-mannanase over the period of 1 and 21 days of age.…”
Section: Resultssupporting
confidence: 80%
“…However, ESONU et al (2004), while studying the inclusion of cellulose enzyme in poultry feed over the period of 28 and 35 days of age, saw an increase in feed intake and decrease in weight gain due to the inclusion of the enzyme. Similarly, OPALINSKI et al (2010) found higher feed intake of broilers fed with a diet including an enzymatic complex containing β-mannanase.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…This finding shows that the anti-nutritional effect is not only restricted to altering the digesta flow but also causes disturbances in the normal functioning of the digestive organs, with increased endogenous secretions such as water, proteins, electrolytes, and lipids (Angkanaporn et al, 1994). Monogastric animals including poultry cannot produce or produce insufficient amounts of the specific enzymes necessary to hydrolyze and digest Non-Starch Polysaccharide present in the cell wall of the grains and they remain unhydrolyzed (Opalinski et al, 2010). In poultry, only the amylase enzyme produced by the pancreas can hydrolyze starch into smaller units that can be absorbed; therefore, the presence of exogenous enzymes is needed (O'NEILL et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The use of enzyme complex in animal feeding improves the utilization of nutrients that would otherwise be unavailable (Leite et al, 2011), reflecting positively on the performance and reducing the pollution load of excreta (Opalinski et al, 2010). However, the inclusion of enzymes in formulations should be made carefully, because this additive may lose their biological activity during pelleting process, which involves high temperatures, moisture, and pressure.…”
Section: Introductionmentioning
confidence: 99%